Моделювання розподілу робіт при системному проектуванні та реінжинірингу виробничих технологічних систем - Чоломбитько, Д. В. (ХНУРЕ, 2024)
This work examines the question of how to efficiently distribute work packages performed in production technological systems. Current work allocation methods have been analyzed and found to be ineffective in real-world practical applications. The work proposes improvement through the development of a multi-criteria model for decision-making taking into account material, time resources and the level of quality of work results. This new approach is expected to significantly increase the efficiency of designing and reengineering complex manufacturing systems.
Keywords: реінжиніринг виробничих технологічних систем; розподіл робіт при проектуванні